Impact of plant canopy structure on the transport of ecosystem entropy - Miedziejko, Ewa M.; Kędziora, Andrzej (Ecological modelling, 2014)
•The subject of analysis was adjustment of the ecosystem structure to exergy dissipation.•The entropy production density is a power function of the leaf area index.•A calculated fractal dimensions suggest the DLA percolation model for exergy dissipation.•Struggle with the entropy produced is inherently involved in the plant biological activity. The continuity of thermodynamic processes taking place in an ecosystem requires downloading incident solar radiation and converting into other forms of energy with simultaneous removal resulting entropy to the environment. For this reason, the struggle with the entropy production requires an adequate plant strategy, probably inherently involved in the biological activity of ecosystems. This hypothesis requires experimental verification. Aim of the work was to make the thermodynamic analysis of energy and entropy balance and exergy efficiency in the cycle of arable crops (forest island, winter wheat, sugar beet and bare soil) development based on the experimental data made in the Agroecological Landscape Park in Turew (West Polish Lowland). Determination of entropy production inside the plant canopy required drawing up a new approach by introducing a combination of experimental field data into the corresponding mathematical model based on the leaf area index (LAI). The studies preformed revealed the ratio of the entropy flux production on the top of ecosystem canopy to the entropy flux production after passage by the plant cover (entropy production density) as power function of the leaf area index (LAI) for all ecosystem's tested. An average value of fractal dimension calculated on the basis of the presented data suggests that DLA (diffusion limited by aggregation) determines the efficiency of entropy removal to the environment. In general, the agricultural landscape ecosystems develop in such a way that provides a systematic increase in their ability to dissipation the exergy taken. The architecture of plant canopy seems to be one of the parameters that control the functioning of ecosystem, due to its unique role in process of entropy removing into the environment.